Robotic lobectomy: an essential addition to the minimally invasive armory - Zhao, Ze-Rui; Ng, Calvin S.H. (Video-Assisted Thoracic Surgery; Vol 1 (August 2016): Video-Assisted Thoracic Surgery, 2016)
As the only robotic system approved by the United States Food and Drug Administration for lung surgery, the Da Vinci System (Intuitive Surgical, Sunnyvale, CA, USA) is gaining popularity worldwide as an important alternative to the conventional minimally invasive surgical approach of video-assisted thoracic surgery (VATS). The robotic system is considered a significant evolution in the development of surgical tools, allowing the surgeon to view the surgical site in three dimensions and perform the operation via a console located near the operating table. The endo-wrist instruments attached to the robotic arms provide a wide range of precision movements with greater dexterity. Moreover, the hand tremor of the surgeon can be filtered out by using a 6-Hz motion filter, which guarantees precise micro-movement around vital structures.